Implikasi dan Implementasi Nilai Islam Pada Mata Pelajaran Bahasa Indonesia di Sekolah Dasar - Zakiah Nasution (Departement of Mathematics Education, 2024)
The importance of studying religious knowledge is linked to mastering scientific knowledge, enabling learning to carry deeper meaning. Islam places a high value on knowledge, requiring every Muslim to pursue education to the fullest extent. One implication of implementing the Merdeka curriculum at the level of Madrasah Ibtidayah or elementary school is the merging of several general subjects into a single theme. This integration naturally creates a gap or dichotomy between general subject areas and Islamic Religious Education (PAI). Therefore, a competency known as integration is necessary, which combines general subjects with the spirit of Islamic values. This study aims to analyze and express the implications and implementation of integrating Islamic values into Indonesian language learning at SDIT Nur Ihsan Medan. The research method used is qualitative with a case study approach. Data collection techniques include interviews, observations, and documentation studies. The findings indicate that the level of integration of Islamic values in Indonesian language learning at SDIT Nur Ihsan Medan encompasses philosophical, methodological and research approach levels, material, strategy, and evaluation levels. A unique aspect of this school is the integration at the communication level. The level of integration at this SDIT also requires support from the teachers' knowledge and understanding of the relationships and applications of Islamic integration in a comprehensive manner, not only in terms of axiological and epistemological levels but also at the ontological level